2023
DOI: 10.1038/s41598-023-45096-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of controlling nutritional status on clinical and survival outcomes in cancer patients treated with immunotherapy

Jiacheng Zhang,
Man Li,
Lilong Zhang
et al.

Abstract: Cancer is a leading cause of death globally. Immunotherapy has shown promise in treating various types of cancer, but its effectiveness varies among patients. The Controlling Nutritional Status (CONUT) score has been linked to the prognosis of different cancers. However, its predictive value for immunotherapy outcomes is not well understood. Our research represents the pioneering meta-study to examine the prognostic value of the CONUT score on cancer patients treated with an immune checkpoint inhibitor (ICI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Researchers have demonstrated that subjects with a lower BMI than obese subjects have a significantly higher abundance of F. prausnitzii [136,137]. On the other hand, other bacteria such as Collinsella [137,138], Veillonellaceae [139], and Lachnospiraceae families are found in significantly higher amounts in subjects > 25 kg/m 2 compared to subjects with typical BMI [137,138,140,141].…”
Section: Associations Of Gut Microbiota Composition With Patient Nutr...mentioning
confidence: 99%
“…Researchers have demonstrated that subjects with a lower BMI than obese subjects have a significantly higher abundance of F. prausnitzii [136,137]. On the other hand, other bacteria such as Collinsella [137,138], Veillonellaceae [139], and Lachnospiraceae families are found in significantly higher amounts in subjects > 25 kg/m 2 compared to subjects with typical BMI [137,138,140,141].…”
Section: Associations Of Gut Microbiota Composition With Patient Nutr...mentioning
confidence: 99%